A facile way to enhance microwave absorption properties of rGO and Fe3O4 based composites by multi-layered structure. (July 2021) - Liu, Mengjia; Liu, Yuhang; Guo, Haichang; Zhang, Bin; Ren, Liucheng; Bashir, Akbar; Bai, Shu-Lin; Ge, Yangyang
Highlights: Microwave absorption performance was highly enhanced through multi-layered distribution of fillers. The improved impedance match and the addition of interfaces contribute to the enhanced microwave absorption properties. The method of combined experimental data with numerical simulation was conducted to ensure the material parameters. The microwave absorption performances can be easily adjusted by thickness to meet different demands. The layered structure can be extended to various materials to improve their microwave absorption performances. Abstract: A facile method to fabricate reduced graphene oxide (rGO) and Fe3 O4 based composites with enhanced microwave absorption property is prepared by adopting multi-layered structure. The optimal effective bandwidth (EB) reaches 8.4 GHz at 5.2 mm, and optimal reflection loss (RL) value achieves −72.7 dB at 4.5 mm. Comparing with the isotropic single-layered composites with no EB at the same condition, there is a distinct improvement of RL values and EB, demonstrating the positive effects of multi-layered structure on the microwave absorption. The highly improved performances mainly ascribe to the extra interfaces and better impedance match. This work remarkably improves the microwave absorption performance of rGO and Fe3 O4 based material through structure adjustment. Besides, we establish an effective and facile path for various materials to enhance their microwave absorption properties by adopting multi-layered structure. The prepared composites can be applied in construction material for microwave absorption and military field for stealth.